Effects of the COVID-19 pandemic on active life behavior of elementary school students in West Java - Beltasar Tarigan; Teten Hidayat (Journal Sport Area, 2022)
The COVID-19 pandemic is transforming human activities, including learning at school. The study aims to analyze the direct effects of the COVID-19 pandemic on the active lifestyle of elementary school students across West Java. In addition, the specific aim of this study is to obtain empirical evidence on active life behavior. The research method in this study is a quantitative descriptive method. The population consists of elementary school students from across West Java and a random sample of 1,867 students from each district. The sampling technique uses a simple random sampling technique. The results shows that the active lifestyle behavior of students during the Covid-19 pandemic is at most distributed in the low category of up to 1,088 people (58%) and before the Covid-19 pandemic the largest distribution is in the moderate category up to 1147 people (61%). These data show that the COVID-19 pandemic is affecting the decline in student active living from the moderate category to the low category.